Dielectric properties of Ni0.2Zn0.8Fe2O4-polypropylene composites - Tan, Foo Khoon; Hassan, Jumiah; Mokhtar, Nurhidayaty; Hashim, Mansor; Ibrahim, Nor Azowa; Wong, Swee Yin; Leow, Chun Yan; Wong, Yick Jeng (Science Publications, 2010)
Problem statement: In the last decade, the studies and investigation on polymer-based composites have drawn significant attention owing to improvement in their mechanical, thermal, electrical, optical and pharmaceutical properties as compared with pure polymer. Approach: Different compositions of Ni0.2Zn0.8Fe2O4 (NZF) and Polypropylene (PP) can alter the useful properties of polymer-based composites. Hence, the determination toward significant percentage of NZF added into PP can improve the dielectric properties of the composites. NZF was prepared using conventional solid-state method and composites of isotactic PP filled with NZF were fabricated. The dielectric properties of the composite were investigated using Agilent 4284A Precision LCR meter. Results: The results indicated that with increasing ratio of wt% NZF, the dielectric constant and dielectric loss of the composite increases. The composition of 30 wt% NZF gave the highest value of the dielectric constant in the frequency range of 100 Hz-10 kHz at room temperature. Conclusion: The incorporation of ceramic filler improved the dielectric constant and increase the dielectric loss of the composite correspondingly increases its potential use as an absorbing material for electromagnetic waves.